Characterizing factors affecting the hot liquid penetration performance of fabrics for protective clothing. Issue 2 (January 2014) - Lu, Yehu; Song, Guowen; Zeng, Hongbo; Zhang, Ling; Li, Jun
Hot liquid hazards present in work environments are well known to be a considerable risk in workplace safety for numerous industries. In this work, the effects of different liquids and temperatures on penetration performance of fabrics were investigated, and the influence of impingement angle on protective performance of liquid penetration was also studied. Several kinds of fabrics for protective clothing were used to characterize the penetration behaviors of protective materials. The results showed the liquid temperature had a significant impact on the stored and penetrated amount of liquids. Different liquids can lead to distinct damage to fabrics. The impingement angle affects liquid transfer (storage and penetration) through the fabric. The addition of a thermal liner or moisture barrier can sharply decrease the penetration. The results provide new insights into the development of functional garments/materials and better methods for evaluating the performance of these materials under hazardous work environments.